2019
DOI: 10.1136/bcr-2018-227718
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-induced stercoral colitis: a surgical perspective

Abstract: We describe a case of a 46-year-old man with schizophrenia treated with clozapine who presented as an emergency with abdominal pain on the background of a 1 month history of constipation. The initial presenting symptoms were vague and a diagnosis was difficult to establish. Initial CT of the abdomen and pelvis demonstrated only minor abnormalities. He continued to deteriorate until a further CT scan revealed worsening stercoral colitis. He subsequently underwent an emergency total colectomy and ileostomy forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Within the individual case reports were 13 cases of PSC with 3 fatalities [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] . There were 9 cases total of NPSC with 4 fatalities [4] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . When the NPSC cases were stratified for sepsis, a total of 4 cases with 2 fatalities was yielded [24] , [25] , [26] , [27] .…”
Section: Clinical Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the individual case reports were 13 cases of PSC with 3 fatalities [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] . There were 9 cases total of NPSC with 4 fatalities [4] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . When the NPSC cases were stratified for sepsis, a total of 4 cases with 2 fatalities was yielded [24] , [25] , [26] , [27] .…”
Section: Clinical Discussionmentioning
confidence: 99%
“…There were 9 cases total of NPSC with 4 fatalities [4] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . When the NPSC cases were stratified for sepsis, a total of 4 cases with 2 fatalities was yielded [24] , [25] , [26] , [27] .…”
Section: Clinical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a reports that ischemia colitis is associated with antiphospholipid syndrome ( 24 ), but reviewing her 20-year history of lupus, no antiphospholipid antibodies were found. In addition, it is reported that some anticonvulsants can induce stercoral colitis ( 25 ), but only one short-term benzodiazepines was used 9 year ago to control a seizure. Importantly, we mainly considered the four neurological events (seizure, cranial neuropathy, transverse myelitis, and brain abscess) lead to impaired nerve innervation and cause neurogenic bladder and chronic constipation, which resulted in this catastrophic stercoral colitis.…”
Section: Discussionmentioning
confidence: 99%
“…The nursing workforce is divided regarding role expansion, and a care gap has opened, leaving the monitoring of patients for possible ADRs, non‐adherence and patient education unattended: doctors and nurses each think the other is or should be doing this work, leading to preventable ADRs (Jordan, 2002), sometimes necessitating hospitalization (NICE, 2015; George et al., 2019; Jordan & Hughes, 2019). We identified dissonance in the data: whilst there was consensus that nurses should expand their roles in these domains and tasks, only ~ 50% nurses were willing to do this.…”
Section: Discussionmentioning
confidence: 99%